Design and implementation of high resolution face image acquisition system under low illumination based on the open source computer vision library - Min Luo; Yadong Luo; Hui Li; Xia Zhang; Yongkui Yang (2017 2nd International Conference on Image, Vision and Computing (ICIVC), 2017)
Super-resolution face image acquisition system is indispensable in people's life. Under the condition of low illumination, the illumination environment difference is too big or the light is insufficient, which leads to the traditional image acquisition system can not collect the high quality face image, and the limitation is poor. Based on open source computer vision library (OpenCV) in the C++ environment configuration, the use of Three Dimension (3D) face recognition technology algorithm, design a set of low illumination conditions of the super resolution face image acquisition system. Experiments show that the design scheme with real-time focusing speed), fast (single acquisition 0.05 seconds), accurate (facial recognition rate of 99.3%) etc. characteristics, be able to fully meet the needs of low illumination conditions for super-resolution of face image acquisition.